The evolution and legitimacy of international security institutions - Cottrell, Patrick (New York : Cambridge University Press, 2016)
International institutions constitute the basis of global order. As they struggle to accommodate shifts in power and emerging threats, their legitimacy - their political authority and right to govern - often comes under fire, at times fuelling perceptions of crisis. Yet scholars seldom ask why some institutions are replaced while others are not. Blending theory with history, M. Patrick Cottrell examines some of the world's landmark security institutions, arguing that the possibility of replacement hinges on the sources of institutional legitimacy and the nature and timing of the challenges to it. The analysis not only reveals different pathways to replacement, but also offers a window into the future, including a potential dark side of too much legitimacy. Indeed, as global society becomes ever more dynamic, the fault lines of conflict with the most significant implications for order will not occur over territory, but rather over the legitimacy of international institutions.
Title from publisher's bibliographic system (viewed on 05 May 2016).
Keywords: Security, International; International cooperation